2019
DOI: 10.3390/pr7020108
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of a High-Turbidity Kaolin Suspension Using Hydrophobic Modified Quaternary Ammonium Salt Polyacrylamide

Abstract: In this work, a novel cationic polyacrylamide (PAMD) was synthesized by acrylamide (AM) diallyl dimethyl ammonium chloride (DMD) and dodecyl polyglucoside (DPL) under low-pressure ultraviolet (UV) initiation. The intrinsic viscosity and cationic degree of PAMD were optimized in copolymerization. The optimum synthesis conditions that affect polymerization were determined to be solid content 30%, DPL content 25%, DMD content 30%, illumination time 135 min, and pH 9. The flocculation performance of flocculant PAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, excessive polymer dosage beyond the optimum level can lead to restabilisation. A previous study reported that the optimum pH of polyaluminium chloride in kaolin suspension was approximately at pH 5–6 (Ma et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive polymer dosage beyond the optimum level can lead to restabilisation. A previous study reported that the optimum pH of polyaluminium chloride in kaolin suspension was approximately at pH 5–6 (Ma et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of synthetic dye remained constant at more than 80% effectiveness. Complexing of Zn 21 with other compounds showed superior coagulation performance in previous studies (Ma et al, 2019). Zinc and phosphate were introduced into iron suspension during the polymerisation process to evaluate their impact on dissolved organic nitrogen removal, which was more than 80%.…”
Section: Introductionmentioning
confidence: 86%
“…Polycation-based flocculation has been established as the primary strategy to remove suspended particles from aquatic media because of several advantages such as simplicity, high efficiency, and low cost . In this respect, polycations such as chitosan and its derivatives, , or cationic derivatives of polyacrylamide, ,, dextran, starch, , and lignin have been thoroughly investigated as flocculants. Such polymers usually interact with the suspended particles via electrostatic attractive interactions and/or van der Waals forces, thus forming larger aggregates which finally undergo sedimentation.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has been widely used in the separation and dehydration of solid/water systems. So far, a large number of flocculants with different functions have been developed for suspended matter removal, sludge dewatering, dye wastewater treatment and heavy metal wastewater treatment [12][13][14]. Cationic polyacrylamide (CPAM) is one of the most widely used flocculants for separating colloidal suspensions.…”
Section: Introductionmentioning
confidence: 99%